Increasing the Security of RFID-based Classroom Attendance System with Shamir Secret Share - Aji Gautama Putrada; Maman Abdurohman (School of Computing, Telkom University, 2020)
This paper proposes an attendance system for increasing the security based on Shamir Secret Share algorithm. The use of RFID devices for classroom attendance is still vulnerable to certain attacks. Students usually make use of existing loopholes for prohibited things, such as forged attendance. Shamir Secret Share is a security method based on the Secure Multiparty Computation (SMC) concept. The SMC guarantees not only the confidentiality of external attacks but also of each member in the secure system. In the attendance scenario using Shamir Secret Share, a student and a lecturer must do tapping at the same time; otherwise, the secret that opens the lock for attendance at that class will not be opened. To realize this system, this paper uses two RFID modules, each of which is connected to one nodeMCU microcontroller. Both systems are connected to a database where the Shamir Shared Secret calculation is performed. Some experiment has been implemented for proving the concept. The result shows that some scenarios of fraud in RFID based attendance can be prevented.